Tourism development potential in an insular territory : the case of Ribeira Grande in the Azores - Couto, Gualter (2019)
The Autonomous Region of the Azores is one of the most sustainable destinations in the world. Being an archipelago comprised of nine small islands, quality and sustainability are critical features in the tourism sector, inducing the need for thorough and technical strategic development processes. Ribeira Grande is an important municipality in the Azores, which envisioned tourism as a strategic sector to develop when the partial liberalization of the air passenger transport sector occurred in 2015. However, this destination had little tourism maturity and competitiveness and required some structural planning work. The development of a strategic plan for tourism for the municipality of Ribeira Grande, including the selection of tourism products, is explained in detail in this article, which highlights the main challenges and results of the process.